2017
DOI: 10.5937/jemc1702097c
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of possibilities for improving entrepreneurial behaviour of young people: Research results in Central Banat district

Abstract: Unemployment, especially among young population, represents one of key economic problems. All important institutions have to be included in overcoming these problems, with the aim of stimulating young people to be involved in entrepreneurial processes. In this paper, global and European trends and trends in the Western Balkans are shown, related to unemployment of young population (aged 15-24). The central part is dedicated to the analysis of possibilities for improving entrepreneurial behaviour of young peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Serbia faces a large set of regulatory and taxation problems, as these create a strong repulsion of the young for any entrepreneurial activity. The lack of motivation among the young in Serbia is due to the lack of starting capital, lack of necessary knowledge, and lack of innovative ideas (Ćoćkalo, Đorđević, Nikolić, Stanisavljev, & Terek, 2017a;Ćoćkalo, Đorđević, Nikolić, Stanisavljev, & Terek, 2017b). These issues should be addressed with introducing financial support and taxation regulations as mentioned before.…”
Section: Resultsmentioning
confidence: 99%
“…Serbia faces a large set of regulatory and taxation problems, as these create a strong repulsion of the young for any entrepreneurial activity. The lack of motivation among the young in Serbia is due to the lack of starting capital, lack of necessary knowledge, and lack of innovative ideas (Ćoćkalo, Đorđević, Nikolić, Stanisavljev, & Terek, 2017a;Ćoćkalo, Đorđević, Nikolić, Stanisavljev, & Terek, 2017b). These issues should be addressed with introducing financial support and taxation regulations as mentioned before.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has been found in a recent study that opportunity-motivated, or pull, entrepreneurship might have become further positive after lockdown restrictions and other measures are relieved (Seah, 2021). It also found that the personal factors of entrepreneurs also significantly affect firms' success (Soomro et al, 2019) various entrepreneurial hurdles need to be reduced (Cockalo et al, 2017;Ćoćkalo et al, 2020). Academicians should create and carry out thorough investigations into the causes and impacts of entrepreneurial motivation (Murnieks et al, 2020).…”
Section: Psychological Motives/motivation and Business Recoverymentioning
confidence: 99%
“…Many authors (Holienka et al, 2016;Green, 2013;Ćoćkalo et al, 2017) have tried to find out what the major incentives are behind the youth entrepreneurial activities. Most of them agree that getting youth population involved in entrepreneurship will create huge value added to the country's economy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study provided by the European parliament (2015) finds that the programs initiated by the state that combines business incubation services and necessary finances trigger young people towards entrepreneurship (Study for the EMPL Committee, 2015). Ćoćkalo, Đorđević, Nikolić, Stanisavljev and Terek (2017) found that as youth unemployment represents one of key economic problems government institutions must take steps to overcome it. Main aim here as authors conclude is to provide stimuli for young people to be involved in entrepreneurial process.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation